PENDIDIKAN ISLAM DI AMERIKA - Krisno; Agussalim (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
The 9/11 tragedy that occurred in the United States, precisely at that time, the World Trade Center building as the center of the United States economy collapsed due to a plane crash that was allegedly controlled by terrorists. After this tragedy, the United States intensively used the media to convey an image of Islam that is synonymous with violence. “Terrorism” and “Islamophobia” are widely discussed. Muslims believe that the United States deliberately did something like this for its political interests. Relations between Islam and the West are heating up. The 9/11 tragedy became one of the world's concerns about Islam. In the Middle Ages, Western countries interacted with Eastern countries which resulted in colonization of Eastern countries. For the sake of colonialism, Western countries needed a variety of knowledge about their society and even their religion, so they sent scholars to study it. This is where the term oriental expert emerged, or what is usually called orientalism.